SEKTE KEAGAMAAN DI LINGKUNGAN PENGIKUT KRISTIANI - Ahmad Jais (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
Religion is considered as an answer to the weakening belief in modernization because modernization is considered to have a negative and destructive impact on human existence as evidenced by the increase in spiritualism among religious followers. The revival of religious spiritualism is not in conventional religions but there is a tendency to enter into spiritual schools, cults and religious sects. Likewise for Christian adherents in Bandung City, West Java. There are several reasons why the author should appoint a religious sect in the Christian Community of Bandung City because Bandung is the center of the movement of Jehovah's Witnesses for seven (7) cities in West Java, so they often mention his movement with the Jehovah's Witnesses or known as JW 07.